Standing Alfvén waves in Jupiter’s magnetosphere as a source of ∼10-60 minute quasi-periodic pulsations - Manners,H; Masters,A; Yates,J (Geophysical Research Letters, 2018)
Energy transport inside the giant magnetosphere at Jupiter is poorly understood. Since the Pioneer era, mysterious quasiperiodic (QP) pulsations have been reported. Early publications successfully modeled case studies of ∼60min (restframe) pulsations as standing Alfvén waves. Since then, the range of periods has increased to ∼10–60 min, spanning multiple data sets. More work is required to assess whether a common QP modulation mechanism is capable of explaining the full range of wave periods. Here we have modeled standing Alfvén waves to compute the natural periods of the Jovian magnetosphere, for varying plasma sheet thicknesses, field line lengths, and Alfvén speeds. We show that variability in the plasma sheet produces eigenperiods that are consistent with all the reported observations. At least the first halfdozen harmonics (excluding the fundamental) may contribute but are indistinguishable in our analysis. We suggest that all QP pulsations reported at Jupiter may be explained by standing Alfvén waves.